2021
DOI: 10.1017/s1047951121001049
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance surrogates and left ventricular hypertrophy in normotensive obese children

Abstract: Background: The relationship between different surrogates of insulin resistance and left ventricular geometry in obese children is still unclear. Objective: We sought to explore the relationship between commonly used measures of insulin sensitivity/resistance (homeostatic model assessment index, serum uric acid, and triglycerides to high-density lipoprotein cholesterol ratio) and left ventricular geometry in normotensive obese children. Methods: In this cross-sectional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…At present, abnormal lipid metabolism leading to left ventricular hypertrophy was explained by the accumulation of lipids in or around myocytes. A study on the human heart showed that fat deposition in the left ventricle constituted a direct risk of myocardial hypertrophy 34 ; abnormal lipid metabolism can be manifested by strong systemic or local inflammation and mitochondrial oxidative stress 35 and/or increased production of reactive oxygen species in NADPH oxidase complex, resulting in oxidative modification of LDL, thereby amplifying the inflammatory potential 36 ; abnormal lipid metabolism was usually accompanied by insulin resistance in the animal model of high‐fat feeding 37 and promoted LVH 38 ; neurohumoral effects 39 included the effects of the sympathetic nervous system, 9 renal angiotensin aldosterone system (RAAS), and other hormones. In addition, other signaling pathways caused by dyslipidemia also played important roles in the development of myocardial hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, abnormal lipid metabolism leading to left ventricular hypertrophy was explained by the accumulation of lipids in or around myocytes. A study on the human heart showed that fat deposition in the left ventricle constituted a direct risk of myocardial hypertrophy 34 ; abnormal lipid metabolism can be manifested by strong systemic or local inflammation and mitochondrial oxidative stress 35 and/or increased production of reactive oxygen species in NADPH oxidase complex, resulting in oxidative modification of LDL, thereby amplifying the inflammatory potential 36 ; abnormal lipid metabolism was usually accompanied by insulin resistance in the animal model of high‐fat feeding 37 and promoted LVH 38 ; neurohumoral effects 39 included the effects of the sympathetic nervous system, 9 renal angiotensin aldosterone system (RAAS), and other hormones. In addition, other signaling pathways caused by dyslipidemia also played important roles in the development of myocardial hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…AI, atherosclerosis index; CI, confidence interval; HT, hypertension; OR, odds ratio; TC/HDL-C, ratio of total cholesterol to high-density lipoprotein cholesterol. (−) represents no or low percentile or low range; (+) represents yes or high percentile or high range.inflammatory potential36 ; abnormal lipid metabolism was usually accompanied by insulin resistance in the animal model of high-fat feeding37 and promoted LVH38 ; neurohumoral effects 39 included the effects of the sympathetic nervous system,9 renal angiotensin aldosterone system (RAAS), and other hormones. In addition, other signaling pathways caused by dyslipidemia also played important roles in the development of myocardial hypertrophy.…”
mentioning
confidence: 99%